Subliminally and Supraliminally Acquired Long-Term Memories Jointly Bias Delayed Decisions - Ruch, Simon; Herbert, Elizabeth; Henke, Katharina (Frontiers in Psychology, 2017)
Common wisdom and scientific evidence suggest that good decisions require conscious deliberation. But growing evidence demonstrates that not only conscious but also unconscious thoughts influence decision-making. Here, we hypothesize that both consciously and unconsciously acquired memories guide decisions. Our experiment measured the influence of subliminally and supraliminally presented information on delayed (30-40 minutes) decision-making. Participants were presented with subliminal pairs of faces and written occupations for unconscious encoding. Following a delay of twenty minutes, participants consciously (re-)encoded the same faces now presented supraliminally along with either the same written occupations, occupations congruous to the subliminally presented occupations (same wage-category), or incongruous occupations (opposite wage-category). To measure decision-making, participants viewed the same faces again (with occupations absent) and decided on the putative income of each person: low, low-average, high-average, or high. Participants were encouraged to decide spontaneously and intuitively. Hence, the decision task was an implicit or indirect test of relational memory. If conscious thought alone guided decisions (= H0), supraliminal information should determine decision outcomes independently of the encoded subliminal information. This was, however, not the case. Instead, both unconsciously and consciously encoded memories influenced decisions: identical unconscious and conscious memories exerted the strongest bias on income decisions, while both incongruous and congruous (i.e., non-identical) subliminally and supraliminally formed memories cancelled each other out leaving no bias on decisions. Importantly, the increased decision bias following the formation of identical unconscious and conscious memories and the reduced decision bias following to the formation of non-identical memories were determined relative to a control condition, where conscious memory formation alone could influence decisions. In view of the much weaker representational strength of subliminally versus supraliminally formed memories, their long-lasting impact on decision-making is noteworthy.